The song of the jade lily : [compact disc, unabridged] a novel - Manning, Kirsty (Harper Audio, 2019)
Two young girls meet in 1939 Shanghai, also known as the 'Paris of the East.' Beautiful local Li and Jewish refugee Romy form a fierce friendship, but the deepening shadows of World War II fall over the women as they slip between the city's glamorous French Concession district and the teeming streets of the Shanghai Ghetto. Yet soon the realities of war prove to be too much for these close friends as they are torn apart. 2016: Fleeing London with a broken heart, Alexandra returns to Australia to be with her grandparents, Romy and Wilhelm. Her grandfather is dying, and over the coming weeks Romy and Wilhelm begin to reveal the family mysteries they have kept secret for more than half a century. As fragments of her mother's history finally become clear, Alexandra struggles with what she learns while more is also revealed about her grandmother's own past in Shanghai.